Cellulose acetate production from paddy rice straw and oil palm empty fruit bunch: trichloroacetate catalyst. Issue 1 (March 2020) - Maryana, R; Anwar, M; Hasanah, S U; Fitriana, E; Suwanto, A; Rizal, W A
Abstract: The utilization of non-wood biomass for fuels and chemicals production is widely studied in recent years. This paper reported the application of trichloroacetate as catalyst in the production of cellulose acetate from paddy (Oriza sativa) rice straw and oil palm (Elaeis guineensis) empty fruit bunch (EFB). Firstly, pre-treatment by using H2 O in acidic condition was carried out prior to the soda pulping by using NaOH 10%, solid to liquid ratio 1:7. The pre-treatment and pulping aim to separate cellulose from lignin and hemicellulose. Furthermore, in order to purify the cellulose, bleaching was applied to the pulps by using NaClO2 0.5% and H2 O2 10%. Finally, the paddy rice straw pulp and oil palm EFB pulp were subjected to the acetylation by using acetic anhydride as acetylating agent in CH3 COOH condition with catalyst CCl3 COOH and H2 SO4 . The analysis results by using Fourier-transform infrared spectroscopy showed that C=O stretching from cellulose acetate at around 1730 cm −1 . Furthermore, the morphological surface and crystallinity of the raw materials and products was analysed by using scanning electron microscopy and X-ray diffraction, respectively. The acetylated cellulose diameter and cristallinity decreased after the acetylation reaction.